Anmeldelse af The Return of Bipolarity in World Politics: China, the United States, and Geostructural Realism - Andersen, Nikolaj K. (Politica, 2019)
Øystein Tunsjø, The Return of Bipolarity in World Politics; China, the United States, and Geostructural Realism. Columbia University Press, 2018 (anmeldt af Nikolaj K. Andersen)